Pemanfaatan Polifenol Teh Hijau (Camellia Sinensis) Sebagai Agen Kemopreventif Kanker Kulit Akibat Paparan Kronis Sinar Uvb - Salsabila Nadhifa Akib (Jurnal Medika Hutama, 2020)
As living things, of course, they need sunlight to live. However, chronic exposure to UV rays without protection can initiate the development of skin cancer. Skin cancer is the most common type of cancer. Skin cancer is divided into two categories of melanoma and non-melanoma skin cancer. This study aims to describe the mechanism of action of green tea polyphenols as chemopreventive agents. The research method used in writing is literature review using 16 articles which can be accessed free of charge at NCBI, ResearchGate, Semantic School from 1997 - 2019. Then, the articles used were analyzed using the systematic literature review method, namely by identifying, reviewing, evaluating, and interpreting all available research on the topic of the researcher's focus. The results showed that the oral and topical administration of green tea polyphenols can be used as a chemopreventive agent in melanoma and non-melanoma skin cancer. The mechanism of green tea polyphenols as chemopreventive agents is explained by their ability to increase the expression of specific nucleotide excision repair (NER) genes (XPA, XPC, RPA1). The NER mechanism will repair nuclear DNA damage in the epidermis and dermis related to the formation of cyclobutane pyrimidine dimers (CPD), inhibit immunosuppression, and inhibit the inflammatory response associated with increased inflammatory markers (COX2, PGE2), markers of epidermal cell proliferation (PCNA, cyclin D1). , and pro-inflammatory cytokine markers (TNF-α, IL-1β, and IL-6).